2003
DOI: 10.1136/gut.52.10.1448
|View full text |Cite
|
Sign up to set email alerts
|

Inducible CD40 expression mediates NF B activation and cytokine secretion in human colonic fibroblasts

Abstract: Background: CD40 has been shown to be a functional activation antigen on a variety of cell types involved in immune responses. As intestinal fibroblasts and myofibroblasts may play a role during mucosal inflammation, we investigated the functional consequences of CD40 induction in primary cultures of human colonic fibroblasts. Methods: Primary colonic lamina propria fibroblasts (PCLF) were isolated from endoscopic biopsies and surgical specimens. Cultures were used between passages 3 and 9. CD40 surface displa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
60
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 55 publications
4
60
0
Order By: Relevance
“…These and other observations make the CD40/CD40L pathway a rational target for therapeutic intervention because disrupting CD40-CD40L interactions, either with blocking Abs or antisense oligonucleotides, could represent a novel approach to turn off intestinal inflammation. Supporting this possibility are reports showing that shutting down the CD40/CD40L system is very effective in dampening inflammation in in vitro cellular systems (7)(8)(9) as well as in vivo in animal models of experimental colitis (16 -19).…”
mentioning
confidence: 59%
“…These and other observations make the CD40/CD40L pathway a rational target for therapeutic intervention because disrupting CD40-CD40L interactions, either with blocking Abs or antisense oligonucleotides, could represent a novel approach to turn off intestinal inflammation. Supporting this possibility are reports showing that shutting down the CD40/CD40L system is very effective in dampening inflammation in in vitro cellular systems (7)(8)(9) as well as in vivo in animal models of experimental colitis (16 -19).…”
mentioning
confidence: 59%
“…12 Subsequently, CD40 was identified on various cell types such as professional APCs, endothelial cells, epithelial cells of different organs, and fibroblasts. 13,14 Its ligand, CD40L, is a 39-kDa surface glycoprotein and a member of the TNF gene superfamily. CD40L is mainly expressed on activated CD4 ϩ T-helper cells and platelets but could also be found on cytotoxic CD8 ϩ T cells.…”
mentioning
confidence: 99%
“…FAF1 could suppress CD40-induced NF κB activation by interacting with the CD40 receptor [26]. And previous studies have demonstrated that CD40 expression level was high in intestinal mucosa and dendritic cells in CD patients [27]. What's more, IFN-γ/CD40L induced cytokine secretion plays an important role in intestinal mucosal inflammation [28].…”
Section: Discussionmentioning
confidence: 99%